Relationships between plasma adiponectin and body fat distribution, insulin sensitivity, and plasma lipoproteins in Alaskan Yup'ik Eskimos: the Center for Alaska Native Health Research study - Goropashnaya, Anna V; Herron, Johanna; Sexton, Mary; Havel, Peter J; Stanhope, Kimber L; Plaetke, Rosemarie; Mohatt, Gerald V; Boyer, Bert B (Metabolism, 2009)
Adiponectin, a protein secreted by adipose tissue, has antiatherogenic, anti-inflammatory, and insulin-sensitizing actions. We examined the relationship between plasma adiponectin and adiposity, insulin resistance, plasma lipids, glucose, leptin, and anthropometric measurements in 316 adult men and 353 adult women Yup'ik Eskimos in Southwest Alaska. Adiponectin concentration was negatively associated with body mass index, percentage of body fat, sum of skin folds, waist circumference, triglycerides, insulin resistance (homeostasis model assessment of insulin resistance [HOMA-IR]), fasting insulin, and leptin in both men and women, and also with glucose in women. Adiponectin concentration correlated positively with high-density lipoprotein cholesterol concentration, and also with low-density lipoprotein cholesterol in women. Insulin-sensitive individuals (HOMA-IR <3.52, n = 442) had higher plasma adiponectin concentrations than more insulin-resistant individuals (HOMA-IR >or=3.52, n = 224): 11.02 +/- 0.27 microg/mL vs 8.26 +/- 0.32 microg/mL, P < .001. Adiponectin concentrations did not differ between groups of participants with low and high level of risk for developing coronary heart disease. No difference in plasma adiponectin levels was found among Yup'ik Eskimos and whites matched for sex, age, and body mass index. In conclusion, circulating adiponectin concentrations were most strongly associated with sum of skin folds in Yup'ik men and with high-density lipoprotein cholesterol levels, sum of skin folds, waist circumference, and insulin and triglycerides concentrations in Yup'ik women.